Case Report: Prenatal presentation of Masson's tumor: first reported case and review of the literature - Tanrıkulu, Bahattin; Erşen Danyeli, Ayça; Özek, M. Memet (Frontiers in Pediatrics, 2026)
Intravascular papillary endothelial hyperplasia (IPEH), or Masson's tumor, is a rare, benign vascular lesion that can closely resemble malignant vascular tumors. While primarily diagnosed in adulthood, pediatric cases are uncommon, and no prenatal diagnoses have been reported to date. Here, we present the first documented prenatal presentation of fetal intracranial IPEH detected in utero at 34 weeks of gestation. This case highlights the importance of considering IPEH in the differential diagnosis of fetal intracranial masses and underscores the role of early prenatal detection in optimizing perinatal and surgical management.